TREATING ALCOHOL WITHDRAWAL SYNDROME - Bethoney, Candice (Acta Scientiae et Intellectus, 2024)
The purpose of this research is to look at the prevention and treatment of AWS in the hospital setting. This paper discusses alcohol misuse and alcohol withdrawal syndrome (AWS). Finally, it includes the exploration of the reasons, signs, and symptoms of AWS.